Intravenous Acetaminophen–Induced Hypotension: A Review of the Current Literature. Issue 10 (October 2019) - Maxwell, Erin N.; Johnson, Brittany; Cammilleri, Joseph; Ferreira, Jason A.
Objective: Recent literature suggests that intravenous (IV) administration may cause hypotension in hospitalized patients; data further suggest that this effect is most pronounced in the critically ill. The purpose of this review is to identify and evaluate current literature that addresses the incidence and implications of IV acetaminophen–induced hypotension.Data Sources: A literature search of MEDLINE, Cochrane, and EMBASE databases was performed (2002-2019) using the following terms: acetaminophen, paracetamol, intravenous, and hypotension . Abstracts and peer-reviewed publications were reviewed.Study Selection and Data Extraction: Relevant English-language studies conducted in humans evaluating the hemodynamic effects of IV acetaminophen were considered.Data Synthesis : A majority of the 19 studies included in this review identified a statistically significant drop in hemodynamic variables after the administration of 500 to 1000 mg IV acetaminophen as measured by changes in systolic blood pressure, diastolic blood pressure, or mean arterial pressure. Of the trials reporting vasopressor use, the authors found a significant increase in vasopressor requirements following IV acetaminophen administration.Relevance to Patient Care and Clinical Practice: This review represents the first comprehensive review of IV acetaminophen-induced hypotension. The findings raise the question of whether IV acetaminophen is an appropriate choice for inpatient pain or temperature management in the critically ill.Conclusions: Available evidence indicates that the administration of IV acetaminophen may be harmful in the critically ill. Additional monitoring is likely required when using IV acetaminophen in this specific population, particularly if a patient is hemodynamically unstable prior to administration.